Idiopathic Subglottic Stenosis during Pregnancy: A Support Group Survey. (February 2021) - McCrary, Hilary; Torrecillas, Vanessa; Conley, Matthew; Anderson, Catherine; Smith, Marshall
Objectives: (1) To determine how pregnancy affects idiopathic subglottic stenosis (iSGS) symptoms. (2) To determine treatments utilized (including operating room (OR) and in-office procedures) for iSGS before, during, and after pregnancy. Methods: A 24-question survey was distributed to an international iSGS support group to assess the patient experience among individuals who have been pregnant with diagnosis of iSGS. Descriptive statistics and chi 2 analyses were completed. Results: A total of 413 iSGS patients participated; 84.7% (n = 350) of patients were diagnosed prior to menopause. A total of 25.5% patients reported being pregnant when they had airway stenosis; 71.1% of those reported more severe airway symptoms during pregnancy. The proportion of patients that reported requiring ≥1 OR interventions (microlaryngoscopy and bronchoscopy, laser, balloon dilation, or steroid injection) before, during and after pregnancy was the following, respectively: 37.3%, 35.6%, 51.3%. Whereas the proportion of patients that reported requiring ≥1 in-office interventions (awake balloon dilation or steroid injection) before, during and after pregnancy was the following, respectively: 13.6%, 11.8%, 15.8%. Number of pregnancies and age of diagnosis was not related to severity of symptoms or requiring more airway interventions ( P  > .05). Conclusions: This survey reveals worsening of symptoms during pregnancy, however, this did not lead to increase in operative or clinic interventions to improve airway symptoms during pregnancy. Future avenues for research include optimizing management of airway symptoms during pregnancy to limit OR-based interventions. Level of evidence: Level IV